2023
DOI: 10.1093/lambio/ovad070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antifungal and antibiofilm activity of postbiotics derived from Lactobacillus spp. on Penicillium expansoum in vitro and in food model

Abstract: Food degradation made by mycotoxigenic molds represents a significant challenge too food security. Postbiotics are associated with soluble compounds liberated by living bacterial cells or their construction release after lysis, and these metabolites offer the host biological action and specific physiological benefits. In this work, the postbiotics from tree strains of Lactobacillus spp. (Limosilactobacillus reuteri ATCC 367, Lacticaseibacillus casei431and Limosilactobacillus reuteri ATCC) were lyophilized, fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Khani et al (2023a) revealed that postbiotics derived from Lactiplantibacillus plantarum had the highest antioxidant properties compared to L . paracasei and L .…”
Section: Evidence Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khani et al (2023a) revealed that postbiotics derived from Lactiplantibacillus plantarum had the highest antioxidant properties compared to L . paracasei and L .…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…The en-FAEN + en-PMLP controlled PV and acidity values, increased antioxidant activity and reduced microbial growth without any negative effects on sensory attributes, consequently leading to the increased shelf life of butter during 60 days of storage at 4°C. Khani et al (2023a) used metabolites derived from Lactobacillus strains as safe additives in the food industry. The postbiotics of L .…”
Section: Evidence Acquisitionmentioning
confidence: 99%